Potential and constraints of little bag silage for smallholders : Results and experiences from Honduras - Reiber, Christoph; Schultze-Kraft, Rainer; Peters, Michael; Hoffmann, Vivian (Cambridge University Press, 2009)
Little bag silage (LBS) is seen as a low-cost alternative suitable for resource-poor smallholders to alleviate dry-season feed constraints. Within a research project carried out by the International Center for Tropical Agriculture and partners in Honduras, LBS was tested and its use encouraged during farmer training and field days. The present study highlights the most relevant technological and socio-economic potential and constraints of LBS. Surveys and experimental results revealed great vulnerability of plastic bags to pests, particularly rodents, accompanied by high spoilage losses. The main constraints to wider adoption include availability of i) suitable and affordable plastic bags, and ii) appropriate chopping equipment and storage facilities on smallholder farms. LBS proved to be useful and could play an important role in participatory research and extension activities, as a demonstration, experimentation and learning tool that can be used to get small-scale silage novices started with a low-risk technology.